The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmicb.2021.698491
|View full text |Cite
|
Sign up to set email alerts
|

Current Methods, Common Practices, and Perspectives in Tracking and Monitoring Bioinoculants in Soil

Abstract: Microorganisms promised to lead the bio-based revolution for a more sustainable agriculture. Beneficial microorganisms could be a valid alternative to the use of chemical fertilizers or pesticides. However, the increasing use of microbial inoculants is also raising several questions about their efficacy and their effects on the autochthonous soil microorganisms. There are two major issues on the application of bioinoculants to soil: (i) their detection in soil, and the analysis of their persistence and fate; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 257 publications
0
26
0
Order By: Relevance
“…Platense seedlings are grown in different plant growth systems after inoculation with diverse strategies applying culture‐dependent and also molecular techniques. As reported [13,14], detection of PGPB once applied adds a piece to the complex puzzle of bio‐input development and enables the selection of an inoculation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Platense seedlings are grown in different plant growth systems after inoculation with diverse strategies applying culture‐dependent and also molecular techniques. As reported [13,14], detection of PGPB once applied adds a piece to the complex puzzle of bio‐input development and enables the selection of an inoculation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Such variation has been attributed to a range of factors or limitations that can affect inoculant survival and establishment. Those may include low quality of commercial inoculants in the absence of universally adopted regulation to guarantee product quality (Manfredini et al, 2021; Salomon et al, 2022), competition with the indigenous AMF community, or abiotic soil conditions (Pellegrino et al, 2015; Hart et al, 2017; Kokkoris et al, 2019; Thomsen et al, 2021). Unfortunately, in most field studies, inoculant establishment is not reported as it is difficult to track the introduced inoculum in indigenous communities (Hart et al, 2017; Manfredini et al, 2021).…”
Section: Nature-mimicry In Soil Biologymentioning
confidence: 99%
“…Those may include low quality of commercial inoculants in the absence of universally adopted regulation to guarantee product quality (Manfredini et al, 2021; Salomon et al, 2022), competition with the indigenous AMF community, or abiotic soil conditions (Pellegrino et al, 2015; Hart et al, 2017; Kokkoris et al, 2019; Thomsen et al, 2021). Unfortunately, in most field studies, inoculant establishment is not reported as it is difficult to track the introduced inoculum in indigenous communities (Hart et al, 2017; Manfredini et al, 2021). Many studies have shown that AMF inoculation has no consistent agronomic benefit where AMF communities are well established (Hart et al, 2017; Bender et al, 2019).…”
Section: Nature-mimicry In Soil Biologymentioning
confidence: 99%
“…Related to the registration requirements, but also useful to design a correct application method, are the needs for methods to detect and monitor bioformulants' strains under natural conditions [111]. Protocols suitable for regulatory or commercial purposes need to be developed to assure a level of discrimination suitable for tracking and monitoring bioformulations in the soil and plants.…”
Section: Fermentation and Formulation Of Bioinoculantsmentioning
confidence: 99%
“…To evaluate the activity of the formulations, several indicators (such as phenological and growth indexes, quality, and yield parameters) are measured, together with a number of microbial and physico-chemical soil properties. All these analyses, having a special focus on soil biodiversity, its dynamics, and the plant-soilmicroorganisms interactions, are expected to highlight the effects of bio-inocula on plant responses to stresses providing bioindicators and supporting the development of molecular diagnostic tools for monitoring the persistence of bio-inocula and their impact on soil and plant-associated biodiversity [111].…”
Section: Challenges Of Field Application Of Microbial-based Productsmentioning
confidence: 99%